Intra-household labor supply, migration, and subsistence constraints in a risky environment: Evidence from rural El Salvador - Timothy J. Halliday (Institute for the Study of Labor (IZA), 2010)
We use panel data from El Salvador to investigate migration and the intra-household allocation of labor as a strategy for coping with uninsured risk. Consistent with a model of a farm household with a binding subsistence constraint, we show that adverse agricultural productivity shocks increased both male migration to the US and the supply of male agricultural labor within the household in El Salvador. In contrast, after damage sustained from the 2001 earthquakes, female migration from El Salvador declined. This is consistent with the earthquakes increasing the demand for home production. Overall, household responses to uninsured risk appear to be consistent with a simple framework in which household members are allocated to sectors according to their comparative advantage. Finally, we show no evidence that the labor market in El Salvador is capable of helping rural Salvadoran households to buffer the effects of adverse shocks.
Keywords: J22; J61; 330; Migration; labor supply; insurance; intra-household allocation; subsistence constraints; Internationale Wanderung; Arbeitsangebot; Haushaltsökonomik; Subsistenzwirtschaft; Risiko; Ländlicher Raum; Erdbeben; El Salvador